Socio-Economics under Female Leadership: Unveiling the History of the Sukadana-Landak Kingdom, 1609-1622 - Patmawati Patmawati; Raziki Waldan; Fitri Susanti Ilyas (istory Department, Faculty of Social Sciences, Universitas Negeri Semarang in collaboration with Masyarakat Sejarawan Indonesia (Indonesian Historical Society), 2026)
Abstract: Studies on the history of Malay kingdoms in West Kalimantan have largely focused on male rulers, leaving female leadership relatively underexplored. This study examines the leadership of Ratu Mas Jaintan in the Sukadana–Landak Kingdom from a socio-economic historical perspective. The research employs a historical method with an interdisciplinary approach integrating social and economic analysis. Data were collected from manuscripts, archival documents, artifacts, oral traditions, and previous studies, supported by field research and analyzed through historical criticism and comparative analysis. The findings show that Ratu Mas Jaintan played a significant role in shaping the socio-economic life of the kingdom by promoting open trade, regulating the use of natural resources such as diamonds and gold, and supporting agricultural activities. These policies strengthened regional trade networks while maintaining social stability and cultural continuity. This study contributes to the historiography of Southeast Asian history by highlighting the strategic role of female leadership in managing economic networks and political authority in Malay kingdoms. It also provides broader implications for understanding gender and power relations in historical governance and the importance of female leadership in socio-economic development in early Southeast Asian societies. Abstrak: Kajian tentang sejarah kerajaan-kerajaan Melayu di Kalimantan Barat selama ini sebagian besar berfokus pada penguasa laki-laki, sehingga kepemimpinan perempuan relatif kurang dieksplorasi. Penelitian ini mengkaji kepemimpinan Ratu Mas Jaintan di Kerajaan Sukadana–Landak dari perspektif sejarah sosial-ekonomi. Penelitian ini menggunakan metode sejarah dengan pendekatan interdisipliner yang mengintegrasikan analisis sosial dan ekonomi. Data dikumpulkan dari naskah, dokumen arsip, artefak, tradisi lisan, serta studi terdahulu, yang didukung oleh penelitian lapangan dan dianalisis melalui kritik sejarah serta analisis komparatif. Hasil penelitian menunjukkan bahwa Ratu Mas Jaintan memainkan peran penting dalam membentuk kehidupan sosial-ekonomi kerajaan dengan mendorong perdagangan terbuka, mengatur pemanfaatan sumber daya alam seperti berlian dan emas, serta mendukung aktivitas pertanian. Kebijakan-kebijakan tersebut memperkuat jaringan perdagangan regional sekaligus menjaga stabilitas sosial dan keberlanjutan budaya. Penelitian ini memberikan kontribusi pada historiografi Asia Tenggara dengan menyoroti peran strategis kepemimpinan perempuan dalam mengelola jaringan ekonomi dan otoritas politik di kerajaan Melayu. Selain itu, penelitian ini juga memberikan implikasi yang lebih luas dalam memahami relasi gender dan kekuasaan dalam tata kelola sejarah, serta pentingnya kepemimpinan perempuan dalam pembangunan sosial-ekonomi pada masyarakat awal Asia Tenggara.